Pharmacogenetic association of the NR1H3 promoter variant with antihypertensive response among patients with hypertension: A longitudinal study - Chen, Yu; Han, Yuqing; Wu, Yiyi; Hui, Rutai; Yang, Yunyun; Zhong, Yixuan; Zhang, Shuyuan; Zhang, Weili (Frontiers in Pharmacology, 2023)
Background: The genetic factors in assessing therapeutic efficacy and predicting antihypertensive drug response are unclear. Therefore, this study aims to identify the associations between variants and antihypertensive drug response. Methods: A longitudinal study including 1837 hypertensive patients was conducted in Northern China and followed up for a median 2.24 years. The associations of 11 candidate variants with blood pressure changes in response to antihypertensive drugs and with the risk of cardiovascular events during the follow-up were examined. The dual-luciferase assay was carried out to assess the effect of genetic variants on gene transcriptional activity. Results: The variant rs11039149A>G in the promoter of nuclear receptor subfamily 1 group H member 3 (NR1H3) was associated with the change in systolic blood pressure (ΔSBP) in response to calcium channel blockers (CCBs) monotherapy. Patients carrying rs11039149AG genotype showed a significant increase of systolic blood pressure (SBP) at follow-up compared with AA carriers, and the difference of ΔSBP between AG and AA carriers was 5.94 mm Hg (95%CI: 2.09–9.78, p = 0.002). In 1,184 patients with CCBs therapy, SBP levels decreased in AA carriers, but increased in AG carriers, the difference of ΔSBP between AG and AA carriers was 8.04 mm Hg (95%CI: 3.28–12.81, p = 0.001). Further analysis in 359 patients with CCBs monotherapy, the difference of ΔSBP between AG and AA carriers was 15.25 mm Hg (95%CI: 6.48–24.02, p = 0.001). However, there was no significant difference in ΔSBP between AG and AA carriers with CCBs multitherapy. The rs11039149A>G was not associated with the cardiovascular events incidence during the follow-up. Additionally, transcriptional factor forkhead box C1 (FOXC1) bound to the NR1H3 promoter containing rs11039149A and significantly increased the transcriptional activity, while rs11039149 A to G change led to a loss-of-function and disabled FOXC1 binding. For the other 10 variants, associations with blood pressure changes or risk of cardiovascular events were not observed. Conclusion: Hypertensive patients with rs11039149AG genotype in the NR1H3 gene have a significant worse SBP control in response to CCBs monotherapy compared with AA carriers. Our findings suggest that the NR1H3 gene might act as a promising genetic factor to affect individual sensitivity to antihypertensive drugs.